1999
DOI: 10.1016/s0033-8389(05)70132-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Carpal Tunnel Syndrome

Abstract: This article presents a new technique for diagnosing carpal tunnel syndrome using ultrasound. The ultrasound characteristics of the normal and abnormal median nerve are discussed in relation to carpal tunnel syndrome. The development of ultrasound as a new diagnostic modality for carpal tunnel syndrome is presented in a three-part study correlating the ultrasound measurements of the median nerve and electromyogram of the median nerve. A new algorithm for evaluating patients with carpal tunnel syndrome is prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(62 citation statements)
references
References 17 publications
2
56
1
3
Order By: Relevance
“…[13] The abrupt change in nerve caliber at the entrance of carpal tunnel is called “notch sign” [Figure 11A and B]. [14] The nerve may show a homogeneous hypoechoic appearance with loss of fascicular echopattern [Figure 12A and B]. On dynamic examination, there is reduced transverse sliding movement in some cases.…”
Section: Entrapment Neuropathiesmentioning
confidence: 99%
“…[13] The abrupt change in nerve caliber at the entrance of carpal tunnel is called “notch sign” [Figure 11A and B]. [14] The nerve may show a homogeneous hypoechoic appearance with loss of fascicular echopattern [Figure 12A and B]. On dynamic examination, there is reduced transverse sliding movement in some cases.…”
Section: Entrapment Neuropathiesmentioning
confidence: 99%
“…These four MR findings are now widely accepted, although they can be nonspecific and observed in asymptomatic individuals [53]. There are various causes of carpal tunnel syndrome, including rheumatoid arthritis, gout, calcium pyrophosphate deposition, acromegaly, hypothyroidism, amyloidosis, neoplasm, ganglion, thrombosis of the median artery, fibrosis of tendons, skeletal anomaly, hemorrhage, and trauma; however, in many cases, the exact etiology remains unidentified [54]. MR imaging can help to identify the causes of carpal tunnel syndrome (Fig.…”
Section: Carpal Tunnel Syndromementioning
confidence: 99%
“…Considering that edema of the nerve is a feature of CTS it follows that the cross-sectional area would be affected, but determining exactly what value is a threshold for CTS requires insight into the normal reference range of the diameter of the nerve, and this is a controversial issue. Different studies have suggested different values for the normal range: 8.5, 9 to 12 (16-18) and even 15 mm 2 (19). In the present study, without consideration of different variables and as a customary rule, the normal range was considered as 8.70 ± 1.56.…”
Section: Discussionmentioning
confidence: 99%